IMPACT OF DIGITAL HEALTH INTERVENTIONS ON QUALITY OF LIFE IN TYPE 2 DIABETES MELLITUS: A SCOPING REVIEW FOCUSED ON INDIAN POPULATIONS - Yuthika Rao; Prof. (Dr.) Manisha Saharan; Dr. Puneet Rhijwani; Prof. (Dr.) Shailendra Mehta (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) adversely affects quality of life (QoL), particularly in low- and middle-income countries such as India. Digital health interventions (DHIs) are increasingly adopted for diabetes self-management, yet their specific impact on QoL outcomes in Indian populations remains underexplored. [3] [12] Objective: To systematically map and synthesize existing literature on the impact of DHIs on QoL among Indian adults living with T2DM. Methods: A scoping review was conducted in accordance with the PRISMA-ScR guidelines. Searches were performed across PubMed, Scopus, Web of Science, and IndMED databases from January 2010 to October 2023. Eligible studies evaluated DHIs—including mobile applications, SMS- based interventions, or telemedicine platforms—and reported QoL outcomes using validated instruments. Data on study design, type of intervention, QoL domains assessed, and outcomes were charted and analyzed narratively. Results: Twelve studies met the inclusion criteria: randomized controlled trials (n=6), quasi- experimental studies (n=3), and pre-post or observational designs (n=3). Interventions included mobile apps, SMS reminders, and teleconsultation-based systems. The most commonly used QoL assessment tools were WHOQOL-BREF, SF-36, and EQ-5D. Ten studies reported statistically significant improvements in at least one QoL domain, with the most consistent benefits observed in physical (9/12 studies) and psychological (8/12) domains. Fewer studies addressed social or environmental QoL. Most interventions were short-term (≤6 months) and conducted in urban settings. [4] [5] [6] Conclusion: DHIs show considerable promise in improving QoL among Indian adults with T2DM, particularly in physical and mental health domains. However, current evidence is limited by short follow-up periods and a lack of focus on rural populations and social determinants. Future research should emphasize long-term outcomes and inclusive, accessible digital design.